Abnormal Adenosine-Induced Immunosuppression and cAMP Metabolism in T Lymphocytes of Patients with Systemic Lupus Erythematosus - Mandler, Raya; Birch, Ruth E.; Polmar, Stephen H.; Kammer, Gary M.; Rudolph, Stephen A. (Proceedings of the National Academy of Sciences - PNAS, 1982)
Normal human T lymphocytes incubated with adenosine (10 μ M) for 30 min at 37 degrees C show an increase in the percentage of cells expressing receptors for the Fc portion of IgG (RFcγ) and the OKT8 antigen, while the proportion of OKT4+cells decreases. These effects occur exclusively in a subset of T cells with theophylline-resistant sheep erythrocyte receptors (TRcells) that is enriched for OKT4+cells. Untreated normal TRcells express helper/inducer cell activity for T-cell-dependent B-cell differentiation, while adenosine-treated TRcells suppress B-cell differentiation. In contrast, in TRcells isolated from patients with systemic lupus erythematosus (SLE), adenosine fails to induce immunosuppressor activity or to increase the percentage of OKT8+and RFcγ +cells. In addition, although incubation of normal TRcells with adenosine causes a transient increase in cAMP levels (up to 160% of control within 5 min), in SLE TRcells, cAMP levels fall by 50% within 10 min. The photoaffinity label 8-azidoadenosine cyclic [32P]monophosphate has been used to show that human T lymphocytes have a single cAMP receptor site that appears to be the regulatory subunit of type I protein kinase. In normal TRcells, this receptor becomes occupied in response to adenosine. In contrast, in SLE TRcells, no change in cAMP receptor occupancy is detected. Although adenosine has a differential effect on normal and SLE TRcells, cAMP derivatives that can traverse the cell membrane (8-bromo- and 8-azidoadenosine cyclic monophosphates) induce an increase in the RFcγ +cell subset in both normal and SLE TRcells. These results suggest that cAMP mediates the effects of adenosine on cell surface markers of T lymphocytes. The lack of an adenosine receptor-coupled adenylate cyclase activity in SLE TRcells may account, in part, for their lack of immunosuppressive activity.